Spin-1/2 Charged Particle in 1+4 dimensions with N=1-Supersymmetry (JOURNAL OF ADVANCES IN PHYSICS, 2015)
We study the dynamics of a charged spin-(1/2) particle in an external 5-dimensional electromagnetic field. We then consider that we are at the TeV scale, so that we can access the fifth dimension and carry out our physical considerations in a 5-dimensional brane. In this brane, we focus our attention to the quantum-mechanical dynamics of the charged particle minimally coupled to the 5-dimensional electromagnetic field. We propose a way to identify the Abraham-Lorentz back reaction force as an effect of the extra ( fifth ) dimension. In another regime of fields allowed by the model, a massive charged particle (CHAMP) behaviour can be, in which the bulk electric field play a crucial rôle.